The Implementation of Religious Moderation Values in Shaping Harmonious Student Character in Secondary Schools - Waslah; Huda, Saihul Atho’ A’laul; Nashihin, Ahmad Ali (Journal of Islamic Education Research, 2025)
This study examines how the implementation of religious moderation values shapes harmonious student character in secondary schools. In a diverse educational setting, promoting tolerance and mutual respect is essential. Using a qualitative descriptive method, data were collected through interviews, observations, and documentation involving school principals, teachers, and students. The findings show that religious moderation is practiced through inclusive programs such as joint religious events, interfaith dialogue, and character-building activities. Teachers play a key role in modeling tolerance and resolving inter-religious tensions constructively. The consistent integration of moderation values fosters student character marked by openness, empathy, and peaceful coexistence. This research contributes to inclusive education practices and offers insights for schools in managing religious diversity effectively. Penelitian ini mengkaji implementasi nilai-nilai moderasi beragama dalam membentuk karakter siswa yang harmonis di sekolah menengah. Dalam lingkungan pendidikan yang beragam, penting untuk menumbuhkan sikap toleran dan saling menghargai. Metode yang digunakan adalah kualitatif deskriptif, dengan teknik wawancara, observasi, dan dokumentasi yang melibatkan kepala sekolah, guru, dan siswa. Hasil penelitian menunjukkan bahwa moderasi beragama diterapkan melalui kegiatan inklusif seperti acara keagamaan bersama, dialog lintas iman, dan pembinaan karakter. Guru berperan penting sebagai teladan dalam menyelesaikan ketegangan antaragama secara konstruktif. Integrasi nilai-nilai moderasi secara konsisten mampu membentuk karakter siswa yang terbuka, empatik, dan mampu hidup berdampingan secara damai. Penelitian ini berkontribusi pada praktik pendidikan inklusif dan memberikan wawasan bagi sekolah dalam mengelola keberagaman secara efektif.